Performance leadership - Leonard, Karen Moustafa; Pakdil, Fatma (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2016)
A daunting aspect of management is the performance appraisal. It has become a byword for unfairness and irritation among employees. Some management writers are even proposing in doing away with it. We agree that the current method of appraisal is unsustainable and counterproductive. In this book, we discuss Performance Leadership--the idea of leading employee performance, which should be the focus of management. Just doing appraisal or evaluation is not enough. Managers must incorporate the entire model of performance management and use it to lead within their workgroup, department, or organization. We walk managers through the steps of Performance Leadership, discussing the benefits and pitfalls of each step. The idea of making performance management work as a leadership style is new and simple, but it takes dedication to complete the task. This book is valuable for supervisors, managers, human resource staff, and others--anyone who needs to manage performance!
1. How is management success created? -- 2. What is performance? -- 3. Are job analysis and job design really necessary? -- 4. How are job descriptions and job specifications created? -- 5. Why use goal setting? -- 6. What is the performance appraisal process? -- 7. Why and how should feedback be given? -- 8. What are major issues in performance leadership? -- References -- Index.
Includes bibliographical references (pages 119-129) and index.
Title from PDF title page (viewed on May 12, 2016).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Performance -- Management; employee appraisal; employee evaluation; feedback; goal setting; human resource management; leadership; management; management skills; managing employees; performance management; SMART goals; SMARTER goals; supervision; top management team support; Electronic books